Environmental DNA (eDNA) metabarcoding as a complementary monitoring tool in cetacean visual surveys: from broad to fine-scale spatial analysis in open waters - Miguel Álvarez-González; Camilo Saavedra; Josep Rotllant; Graham J. Pierce; Paula Gutiérrez-Muñoz; José Antonio Vázquez Bonales; Paula Suarez-Bregua (Marine Environmental Research, 2026)

Selectivity-based management for reversing overexploitation of demersal fisheries in North-western Mediterranean Sea - N. Bahamon; L. Recasens; J. Sala-Coromina; B. Calero; J.A. Garcia; G. Rotllant; A. Maurer; A. Rojas; L. Muth; J. Quevedo; M. Vigo; J. Ribera-Altimir; et al. (Marine Policy, 2024)

Environmental DNA (eDNA) for monitoring marine mammals: Challenges and opportunities - Paula Suarez-Bregua; Miguel Álvarez-González; Kim M. Parsons; Josep Rotllant; Graham J. Pierce; Camilo Saavedra (Frontiers in Marine Science, 2022)
Monitoring marine mammal populations is essential to permit assessment of population status as required by both national and international legislation. Traditional monitoring methods often rely on visual and/or acoustic detections from vessels and aircraft, but limitations including cost, errors in the detection of some species and dependence on taxonomic expertise, as well as good weather and visibility conditions often limit the temporal and spatial scale of effective, long-term monitoring programs. In recent years, environmental DNA (eDNA) has emerged as a revolutionary tool for cost-effective, sensitive, non-invasive species monitoring in both terrestrial and aquatic realms. eDNA is a rapidly developing field and a growing number of studies have successfully implemented this approach for the detection and identification of marine mammals. Here, we review 21 studies published between 2012 and 2021 that employed eDNA for marine mammal monitoring including single species detection, biodiversity assessment and genetic characterization. eDNA has successfully been used to infer species presence (especially useful for rare, elusive or threatened species) and to characterize the population genetic structure, although additional research is needed to support the interpretation of non-detections. Finally, we discuss the challenges and the opportunities that eDNA could bring to marine mammal monitoring as a complementary tool to support visual and acoustic methods.

Population structure and reproductive patterns of the NW Mediterranean deep-sea macrourid Trachyrincus scabrus (Rafinesque, 1810) - U. Fernandez-Arcaya; L. Recasens; H. Murua; E. Ramirez-Llodra; G. Rotllant; J. B. Company (Marine Biology, 2012)

Biological patterns and ecological indicators for Mediterranean fish and crustaceans below 1,000 m: a review - F. Sardà; J. B. Company; G. Rotllant; M. Coll (Reviews in Fish Biology and Fisheries, 2009)

Environmental influences on zooplankton and micronekton distribution in the Bransfield Strait and adjacent waters - I. A. Catalán; B. Morales-Nin; J. B. Company; G. Rotllant; I. Palomera; M. Emelianov (Polar Biology, 2008)

Ligand binding and signalling pathways of PTH receptors in sea bream (Sparus auratus) enterocytes - J. Rotllant; P. M. Guerreiro; B. Redruello; H. Fernandes; L. Apolónia; L. Anjos; A. V. M. Canario; D. M. Power (Cell and Tissue Research, 2006)

Synchronous moulting of krill, Euphausia superba , in the Bransfield Strait (Antarctica) - G. Rotllant; J. B. Company; X. Busquets; F. Buchholz (Polar Biology, 2004)

Differences in interrenal tissue, biosynthetic capacity and ACTH sensitivity in progeny of sea bream from parents selected for high or low cortisol response - J. Rotllant; D. Montero; M. J. Caballero; L. Robaina; M. S. Izquierdo; L. Tort (Journal of Fish Biology, 2003)
Progeny of sea bream Sparus aurata from parents selected for high or low cortisol response to stress also showed similar divergent cortisol response after 48 h of handling and confinement stress. The high response progeny, however, had a lower basal unstimulated cortisol release and ACTH‐stimulated cortisol output in vitro .

A drop in ambient temperature results in a transient reduction of interrenal ACTH responsiveness in the gilthead sea bream (Sparus aurata, L.) - J. Rotllant; P.H.M. Balm; S.E. Wendelaar-Bonga; J. Pérez-Sánchez; L. Tort (Fish Physiology and Biochemistry, 2000)

Inhibition of HPI axis response to stress in gilthead sea bream (Sparus aurata) with physiological plasma levels of cortisol - J. Rotllant; R.J. Arends; J.M. Mancera; G. Flik; S.E. Wendelaar Bonga; L. Tort (Fish Physiology and Biochemistry, 2000)

Modulation of the response of rainbow trout (Oncorhynchus mykiss Walbaum) to confinement, by an ectoparasitic (Argulus foliaceus L.) infestation and cortisol feeding - N.M. Ruane; D.T. Nolan; J. Rotllant; L. Tort; P.H.M. Balm; S.E. Wendelaar Bonga (Fish Physiology and Biochemistry, 1999)

Cortisol and glucose responses after acute stress by net handling in the sparid red porgy previously subjected to crowding stress - J. Rotllant; L. Tort (Journal of Fish Biology, 1997)
In red porgy Pagrus pagrus subjected to 3 weeks of chronic stress by crowding, plasma cortisol remained significantly higher in crowded fish compared to controls. There was no significant effect of crowding on plasma glucose levels. When the crowded fish were subjected to an acute handling the plasma cortisol response was similar to that of the uncrowded fish. No significant differences were found between the groups. The changes in plasma glucose following acute handling were also similar in both crowded and uncrowded fish.